Surgery, Chemotherapy and Radiotherapy May Promote Cancer Growth Speeds and Shorten Patient Lives - Jianqing Wu; Ping Zha (Global Journal of Cancer Therapy - Peertechz Publications, 2022)
Medicine fails to find predictable cures for cancer in more than a century, and we explored the feasibility of controlling cancer growth speed by using lifestyle factors. After conducting an extensive literature review, we conducted simulations for cancer growth courses to see the feasibility of controlling cancer growth speeds. We found that (1) medical treatments are often accompanied by three to four lethal factors: treatment side-effects, emotional distress, and chronic stress, reduced exercises and physical inactivity, and excessive nutrition in some cases; (2) clinical trial exaggerates treatments short-term benefits and underestimates the slow-delivering adverse side effects as a result of statistical averaging, interfering effects of personal lifestyle factors and insufficient follow-up times; (3) the benefits of medical treatments are limited by chain comparisons, where surgery may work as a negative standard relative to the best alternatives for resolving cancer; (4) the strategy of destroying the tumor or killing all cancer cells is unworkable; (5) medical treatments can turn natural cancer growth curve into approximately doubly exponential curve; (6) multiple-factor non-medical measures are potentially much more powerful than medical treatments in controlling cancer growth and metastasis speeds; and (7) cancer early diagnosis and over treatments are unwise strategies in light of discoveries. Based on huge increases in cancer growth rate constants, substantial loss of vital organ functional capacity, and severe systemic aging-like cellular damages, we concluded that medical treatments may promote cancer growth and metastasis speeds and shorten patient lives in most situations, and the claimed benefits are caused by triple biases of clinical trials. By using the same method to explore how several lifestyle factors affect cancer growth rates, we concluded that the better strategy for ending the global cancer epidemic in the future is changing caner treatment strategy from killing cancer cells to slowing down cancer growth rates by using various lifestyle factors in combination. This study in part explains why cancer can self-resolve.